PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA APARATUR DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN CIAMIS - Palls, Aswin (Prodi Administrasi Publik FISIP UNPAS, 2020)
Organizational culture provides identity for members of the organization and evokes commitment to beliefs and values ​​that are greater than itself. Organizational culture needs to have values, norms, guidelines that must be implemented. These values ​​and beliefs will be realized through the employee's daily behavior at work. Problems related to the influence of organizational culture on performance in the Human Resources and Human Resources Development Agency of Ciamis Regency, which is seen from the timeliness indicator where the apparatus paid little attention to the timeliness of work and efficient work in the report of the Employee Work Unit. This is because the organizational culture has not been fully implemented based on the prime characteristics of organizational culture including stability. The research method used is the Explanatory Survey research method using quantitative analysis, while the questionnaire technique using Accidental Sampling technique is distributed to 30 respondents. The results show that organizational culture has a close influence on performance in the Ciamis Regency Human Resources Development and Human Resources Development Agency, this influence is positive, meaning that the organizational culture in the Human Resources and Human Resources Development Agency of Ciamis Regency if applied in accordance with the characteristics organizational culture well, the performance of the Apparatus at the Human Resources and Human Resources Development Agency of Ciamis Regency will increase. The constraints faced by the Ciamis Regency Human Resources and Human Resources Development Agency are as follows: The unclear information conveyed by each of the leaders of the organization's sub-section to the apartment, the lack of firmness from the head of the agency and the section head to the apparatus to be on time to complete the work and lacks good cooperation between employees because they are more concerned with individual work completion. The efforts made to overcome the obstacles are as follows: The organization needs to provide information to the apparatus clearly, so that the information can be received and implemented by the entire apparatus so that there will be no misunderstanding or interpretation, the head of the body and the section head need to be more assertive Again in dealing with the apparatus by giving stricter regulations again also giving a good reflection on the apparatus, the head of the agency or the head of the field needs to pay more attention to the apparatus in completing each job so that it can be seen whether the apparatus is careful in completing the work or not. Key Words: Organizational Culture, Apparatus Performance